The karate kid. Part III [videorecording (DVD)] - Avildsen, John G., 1935-2017; Macchio, Ralph, 1961-; Morita, Pat, 1932-2005; Kanan, Sean. 1966-; Griffith, Thomas Ian (Columbia Tristar Home Entertainment, 2001)
The Karate Kid Daniel LaRusso (Macchio), has an upcoming tournament in which he is the target of vicious student Mike Barnes (Kanan). Mr. Miyagi (Morita) instructs LaRusso not to compete, but LaRusso's pride sends him to instructor Terry Silver who is secretly setting LaRusso up to be the loser.